Root resorption in Orthodontics : A review - KiruthikaPatturaja; Kumar, Naveen; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Root resorption is an unavoidable pathologic consequence of orthodontic tooth movement. Force application initiates a sequential cellular process. The onset and progression of root resorption are associated with risk factors related to the orthodontic treatment such as the duration of treatment, the magnitude of the force applied, the direction of the tooth movement, the method of force application during orthodontic treatment. This review aims to find root resorption in patients who had orthodontic tooth movement based on the currently used advances in orthodontic brackets and aligners and knowledge of the mechanical ,biological aspects and ways to prevent root resorption in orthodontic tooth movement among general practitioners .